Harga Impact Aluminium Jenis 7075 T351 Dengan Metode Charpy - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Rofarsyam, Sukarman (Teknis, 2015)
This study aims to determine the kind of big impact aluminium 7075 T351, and prove material temperature betweenÂ â 8 oC to 100 oC there was no significant difference in shock loads. Testing was conducted using Charpy, the sample size and temperature variations. Variation in the sample size standard ASTM E23, while the corresponding temperature variations not the temperature of the load shock. Large impact loads generated 0,24705828 Joule/mm2 and its potential energy 20,175625 Joule. Then based on the temperature and the load shows that the temperature with impact loads no significant correlation.Keywords: impact, charpy, aluminium 7075 T35